Therapeutic Mechanism and Clinical Observation of Traditional Chinese Medicine Combined with Interventional Recanalization for Tubal Infertility - Can Liu (Hindawi Limited, 2021)
To observe the clinical effect of traditional Chinese medicine (TCM) combined with interventional recanalization therapy in the treatment of tubal obstructive infertility, first, different treatment approaches were used on rabbits, and transmission electron microscopy (TEM) indicated that interventional recanalization combined with TCM can significantly ameliorate the pathological condition of the fallopian tube after treatment. Moreover, ELISA disclosed that the treatment could significantly reduce the levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) and increase the expression of interleukin-10 (IL-10), which demonstrated that TCM therapy can help against inflammation of the fallopian tubes. PCR array analysis revealed that BMP4, BMPR1A, SMAD2, SMAD3, SMAD4, and KLF10 expressions were upregulated, and SMAD7 expression was downregulated, proving that combined treatment could influence gene expression in the TGF-β family and further regulate the secretion of proteins in SMADs. In addition, a clinical study recorded the fallopian tube patency rate of 165 patients after 12 months. The recanalization rates in the two groups were 81.9% and 53.1%, with the higher rates in the combined medicine enema group. All these findings implied that interventional recanalization combined with TCM preparation has a stronger effect. The mechanism probably involves effects on the expression of genes in the TGF-β/SMAD and BMP/SMAD signaling pathways, with simultaneous regulation of inflammatory factors, thereby improving the ovarian environment and increasing pregnancy rates.